Regional anesthesia in obese patients: Challenges, considerations, and solutions - Alessandro De Cassai; Francesco Zarantonello; Elisa Pistollato; Tommaso Pettenuzzo; Veronica Busetto; Nicolò Sella; Annalisa Boscolo (Saudi Journal of Anaesthesia)
The increasing global prevalence of obesity has significant implications for anesthesiologists, particularly in the context of regional anesthesia. Anesthesiologists face numerous challenges during anesthesia in obese patients, including compromised respiratory function, altered pharmacokinetics of local anesthetics, and difficulties in identifying anatomical landmarks. Obesity often leads to reduced respiratory reserve, increased risk of hypoventilation, and conditions such as obstructive sleep apnea syndrome and obesity hypoventilation syndrome, which increase the likelihood of postoperative complications. Additionally, altered body composition in obese patients affects the distribution of local anesthetics, requiring adjustments in dosing based on lean body weight rather than total body weight. Furthermore, excess adipose tissue complicates the identification of anatomical landmarks and the use of ultrasound for regional block procedures, as the increased tissue depth and reduced image resolution hinder needle placement. Proper positioning, the use of low-frequency transducers, and harmonic imaging techniques are essential for optimizing ultrasound guidance. Additionally, the use of longer needles and the application of trigonometric calculations based on ultrasound scans can help determine the appropriate needle length. To overcome these challenges, anesthesiologists should adopt strategies that involve adjusting drug dosages, utilizing specialized equipment, and continuously monitoring patients for potential complications. A holistic approach involving knowledge of these technical and pathological challenges, as well as adapting techniques and equipment, is crucial for ensuring the safety and effectiveness of regional anesthesia in obese patients.